(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article presents a method of triadic decryption for the organization of knowledge due to consistent detailing in the forms of triads of categories in relation to the management sphere. The application of the triadic decryption method to solve the problem of determining the directions of strategic development of a food industry manufacturing enterprise is considered. The possible directions of the formation of the strategy of the production enterprise are identified, their characteristics are given, and the features are considered.